Analysis of Earnings Quality and Enterprise Valuation of Microsoft by Earnings Quality and Residual Income Model - Jiang, Ruitao (Transactions on Economics, Business and Management Research, 2024)
Artificial intelligence has had a remarkable influence in recent years and has developed many revolutionary solutions in many industries. OpenAI’s ChatGPT is one of the most popular products in this trend. As the largest stockholder of OpenAI, Microsoft has committed itself to integrating artificial intelligence into its primary products, like Microsoft Office and Azure. Although Microsoft experienced a continuous slump in stock in 2022, Microsoft’s current stock price has broken through $400 per share. This paper aims to conduct a financial analysis and forecast Microsoft’s future growth to figure out Microsoft’s intrinsic value. This article uses earnings quality analysis and residual income model to evaluate Microsoft’s financial performance and conduct valuation. Microsoft’s Cash Conversion Cycle has become negative since 2021, so Microsoft can reinvest the cash it receives from sales before using it to pay suppliers. The present value of the continuing value in the Residual Income Model indicates that Microsoft is undervalued compared to the current stock price. Economic conditions and the global supply chain will also influence investors’ expectations, except for quantitative factors. Therefore, Microsoft's stock price fluctuates and does not exceed the forecasted price. This article offers some insights on Microsoft and relevant industry valuation analysis.